Matters of perspective; Local visual expertise and natural history drawings in Java, 1820-1850 - Weber, Andreas; Zanen, Sylvia van (Wacana, Journal of the Humanities of Indonesia, 2022)
This essay examines how local draughtsmen using their visual expertise shaped natural historical knowledge production in colonial Indonesia in the early nineteenth century. The persons at the core of this essay are Tsing Wang Ho and Pieter van Oort, both draughtsmen who worked for the Natuurkundige Commissie voor Nederlandsch-Indië (Committee of Natural History of the Netherlands Indies). By zooming in on the Committee’s fieldwork in Java in the 1830s, this essay highlights that producing scientific drawings of animals and plants was a challenging endeavour. Despite detailed instructions from Europe and the logistical support of the colonial government in Batavia, the success of the Committee’s fieldwork also depended on local visual and natural expertise. By shifting the analytical focus from European draughtsmen and naturalists to local visual and natural expertise, this essay offers readers glimpses on a cross-cultural learning process which, in the long run, reshaped the visual repertoire on which taxonomic and biodiversity research has since then built on.